Effects of dietary Leucine supplementation on intestinal development and gene expression of pattern recognition receptors (PRRs) in broilers - Xue Pan; Jie He; Okasha Hamada; Johan Buyse; Zhigang Song; Lixian Zhu (Poultry Science)
This study investigated the effects of 0.4 % Leucine (Leu) addition on growth performance, intestinal growth, carcass characteristics, and pattern recognition receptors (PRR) gene expression in broilers. A Total of 144 one-day-old Arbor Acres broilers were randomly divided into two treatment groups: the basal diet (CON) and the basal diet added with 0.4 % crystalline Leu. Growth performance, visceral organ indices, carcass traits, intestinal growth, and mRNA levels of TLR2, TLR4, NOD1, NOD5, and IL-4 were analyzed at 20 and 40 d. Results indicated that Leu reduced the FCR during 1-20 d (P < 0.05) and increased ADG during 21-40 d (P < 0.05). Leu increased IL-4 expression in the duodenum and jejunum and enhanced relative intestinal weight and length during the starting phase (20 d) (P < 0.05). Leu downregulated the gene expression of NOD1, NOD5, and TLR4 in the duodenum (P < 0.05) and reduced the jejunal mRNA levels of NOD1 (P < 0.05). At 40 d, Leu increased pectoral muscle yield and downregulated TLR4 in pectoral muscle (P < 0.05). These findings suggest that dietary Leu supplementation improves intestinal development and modulates PRR-related immune responses in a tissue-specific manner, highlighting its potential as an immunomodulatory feed additive.